ADVANCE CARE PLANNING FROM THE CONSUMERS PERSPECTIVE: THE MAKING OF A DVD. Issue 2 (1st June 2013) - Billings, S; Nicholes, M; Gill, L; Van Es, H
Abstract : Background: RealTime Health is a Melbourne-based online health content producer, specialising in the niche area of 'patient and carer narrative'. Alfred Health Advance Care Planning (ACP) Service partnered with Realtime Health to make a DVD on the patient and carer experience of going through the process of Advance Care Planning. Aim: To produce a consumer driven DVD on ACP that can be utilised as a marketing and education tool for consumers, health care professionals and community groups. Methods: Five consumers and carers were recruited and went through a consent process to participate in the DVD. Each person was chosen because of their unique background to illustrate a variety of experiences such as caring for someone with dementia and making difficult decisions for someone who is dying. The interviews were unscripted which allowed for a natural flow of information. Results: The DVD will be showcased on the Realtime Health website in their 'Speaking form Experience' series, which comprises an extensive database for a range of illnesses/health issues which is easily accessed by Health Care Professionals and the general public. Alfred Health will have video clips inserted onto the ACP internet and intranet pages and this will be utilised as client, staff and community based education. Conclusion: Hearing first hand accounts from real people that have lived through an experience is powerful and thought provoking. We hope to motivate individuals to consider doing ACP for themselves.